K0sK0s correlations in pp collisions at √s=7 TeV from the LHC ALICE experiment* - Abelev, Betty; Angelov, Venelin; Busch, Oliver; Engel, Heiko; Glässel, Peter; Grajcarek, Robert; Herrmann, Norbert; Krawutschke, Tobias; Kweon, MinJung; Lara Martinez, Camilo Ernesto; Lohner, Daniel; Mercado Pérez, Jorge; et al. (Physics letters, 2012)
Identical neutral kaon pair correlations are measured in s=7 TeV pp collisions in the ALICE experiment. One-dimensional Ks0Ks0 correlation functions in terms of the invariant momentum difference of kaon pairs are formed in two multiplicity and two transverse momentum ranges. The femtoscopic parameters for the radius and correlation strength of the kaon source are extracted. The fit includes quantum statistics and final-state interactions of the a0/f0 resonance. Ks0Ks0 correlations show an increase in radius for increasing multiplicity and a slight decrease in radius for increasing transverse mass, mT, as seen in ππ correlations in pp collisions and in heavy-ion collisions. Transverse mass scaling is observed between the Ks0Ks0 and ππ radii. Also, the first observation is made of the decay of the f2′(1525) meson into the Ks0Ks0 channel in pp collisions.